One Summer America - Bill Bryson (Doubleday, 2013)
In the summer of 1927, America had a booming stock market, a president who worked just four hours a day (and slept much of the rest of the time), a semi-crazed sculptor with a mad plan to carve four giant heads into an inaccessible mountain called Rushmore, a devastating flood of the Mississippi, a sensational murder trial, and a youthful aviator named Charles Lindbergh who started the summer wholly unknown and finished it as the most famous man on earth. (So famous that Minnesota considered renaming itself after him.) It was the summer that saw the birth of talking pictures, the invention of television, the peak of Al Capone's reign of terror, the horrifying bombing of a school in Michigan by a madman, the ill-conceived decision that led to the Great Depression, the thrillingly improbable return to greatness of a wheezing, over-the-hill baseball player named Babe Ruth, and an almost impossible amount more. In this hugely entertaining book, Bill Bryson spins a story of brawling adventure, reckless optimism and delirious energy, with an unforgettable cast of vivid and eccentric personalities.